A Study on Iterative Algorithm for Stochastic Distribution Free Inventory Models. (19th March 2013) - Lin, Jennifer
Abstract : We studied the iterative algorithm in Tung et al. (2010) to find out that their assertion is questionable. We derived two new relations between safe factor and order quantity so that we can execute the iterative algorithm proposed by Wu and Ouyang (2001). We have proved that three generated sequences indeed converge to provide a theoretical validation for their iterative procedure.